VALEA IERII’S RIVERBED DYNAMICS AND THE NECESSITY OF ITS RECONFIGURATION WITH THE AIM OF CREATING AN ECOLOGICAL CORRIDOR - CEORNEI, Alexandra; MĂCICĂȘAN, Vlad; ROSIAN, Gheorghe (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
The evolution of Valea Ierii’s riverbed from the perspective of erosion and alluvial deposits influences the configuration of the habitat of alluvial forests with Alnus glutinosa and Fraxinus excelsior. This habitat presents a great number of species protected by the European legislation. This study presents the rehabilitation of Valea Ierii’s riverbed characteristics with the aim of creating a linear and continuos corridor. Even if this concept is not entirely investigated at local and global level, the submitting and the implementation of this type of natural structure endorses the sustainable development. As a result of this research, we applied geomorphological, cartographical and ecological methods for 3 different sections chosen in the field. This paper presents a series of discussions and propositions for the support and conservation of biodiversity. To this effect, we analyzed the evolution of the studied area by making a simulation of the river course and the habitat structure for the following 15 years.